An Interdisciplinary Approach to the Human Mind Subjectivity, Science and Experiences in Change - Joranger, Line (Taylor & Francis, 2018)
One of the main aims of modern mental health care is to understand a person's explicit and implicit ways of thinking and acting. So, it may seem like the ultimate paradox that mental health care services are currently overflowing with brain concepts belonging to the external, visible brain-world and that neuroscientists are poised to become new experts on human conduct. An Interdisciplinary Approach to the Human Mind shows that to create care that is truly innovative, mental health care workers must not only ask questions about how their conceptions of human beings and psychological phenomena came into being, but should also see themselves as co-creators of the mystery they seek to solve.